Signifikansi Peristiwa Malari 74: Mahasiswa dalam Lanskap Politik Indonesia - Donny Maulana; Hariyono Hariyono; Indah Wahyu Puji Utami; Aditya Nugraha Widiadi; Arif Subekti (Universitas Tribhuwana Tunggadewi, 2026)
The New Order's economic policy, which relied on foreign investment (PMA) and foreign debt (IGGI), paradoxically engendered dependency, sharp socio-economic inequality, and the marginalization of domestic enterprises, despite its success in curbing inflation. This research aims to analyze the historical significance of the 1974 Malari Incident as the culmination of public unrest spearheaded by students. Employing Kuntowijoyo's historical research method, this study examines primary sources, such as archives and contemporary news reports, as well as secondary literature. The findings reveal how discontent over the impacts of development was successfully consolidated by figures like Hariman Siregar, transforming sporadic actions into a solid mass movement. This movement raised the central issues of the dominance of foreign capital, particularly from Japan, and the controversial role of the presidential Personal Assistants (Aspri). In conclusion, the fundamental significance of the Malari Incident transcends that of a momentary political protest. The event reaffirms the historical thesis that national consciousness and responsibility are a calling for every intellectual, regardless of their academic discipline a principle reflected by medical and engineering students during the national movement era. They are called to